COPYRIGHT AWARENESS OF DOCTORAL STUDENTS IN CALICUT UNIVERSITY CAMPUS - Dr. Vasudevan T. M AND Suchithra K. M (International Journal of Digital Library Services, 2013)
This paper focused on copyright awareness of doctoral students in Calicut University Campus. A structured questionnaire was distributed among 120 doctoral students in the Calicut University campus. Out of 120, 60 from science departments and 60 from non-science departments. The study revealed that majority of the doctoral students are aware about copyright law and its importance, but the study also revealed that a good number of the doctoral students are less aware about plagiarism. The study also helped the investigators to reach at the conclusion that copyright is relevant in digital environment.